Toxicological Implications of Platinum Nanoparticle Exposure: Stimulation of Intracellular Stress, Inflammatory Response, and Akt Signaling In Vitro - Claudia J. Labrador-Rached; Rebecca T. Browning; Laura K. Braydich-Stolle; Kristen K. Comfort (Journal of Toxicology)
Due to their distinctive physicochemical properties, platinum nanoparticles (PtNPs) have emerged as a material of interest for a number of biomedical therapeutics. However, in some instances NP exposure has been correlated to health and safety concerns, including cytotoxicity, activation of cellular stress, and modification to normal cell functionality. As PtNPs have induced differential cellular responses in vitro, the goal of this study was to further characterize the behavior and toxicological potential of PtNPs within a HepG2 liver model. This study identified that a high PtNP dosage induced HepG2 cytotoxicity. However, lower, subtoxic PtNP concentrations were able to elicit multiple stress responses, secretion of proinflammatory cytokines, and modulation of insulin-like growth factor-1 dependent signal transduction. Taken together, this work suggests that PtNPs would not be overtly toxic for acute exposures, but sustained cellular interactions might produce long term health consequences.